The use of the KTP 532 nm vascular laser in the treatment of erythema and telangiectasia caused by low temperature exposure - case report - Kozińska, Urszula; Gras-Ozimek, Jordi; Gras-Ozimek, Aleksander; Skwira, Sylwia; Oleszczuk, Rafał (Journal of Education, Health and Sport, 2022)
The use of the KTP 532 nm vascular laser in the treatment of erythema and telangiectasia caused by low temperature exposure - case report. A case report. The paper presents a case of effective treatment of frostbite vascular lesions in the face with the use of a 532nm KTP laser in a 55-year-old man with a long history of skin exposure to low temperatures. Aim. The aim of this study is to draw attention to the possibility of using laser therapy in the treatment of skin disorders that are a complication of exposure to low temperatures. In the article below, we present the reduction of vascular lesions of the facial skin during a series of laser treatments with the use of the 532nm laser, meeting the growing interest of patients and doctors in the use of laser therapy in the treatment of skin vascular lesions. Conclusions. The use of laser therapy with the KTP 532nm laser can be an important and effective element in the treatment of skin vascular lesions.